TO THE METHODOLOGY OF ANALYZING THE FINANCIAL AND ECONOMIC SECURITY OF BUSINESS ENTITIES - VASYLTSIV, Taras; CHUY, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is the further development of the methodology for analyzing the financial and economic security of economic entities. Increased attention to the issue of ensuring the financial and economic security of economic entities in today’s complex conditions of economic uncertainty. The role and significance of the application of progressive tools for analyzing and evaluating the financial and economic security of business entities is emphasized. The characteristic of the indicator approach to the analysis of financial and economic security is given. The advantages and disadvantages of using the resource-functional approach to analyzing the financial and economic security of enterprises are indicated. It has been proven that the most unsecured aspects in the analysis of financial and economic security are the formation of a system of analysis indicators, as well as the substantiation of their limit values. It was established that today a single recognized approach to the analysis and assessment of the financial and economic security of business entities has not yet been developed, but the significance of this is critically high in the sense of the formation of high-quality management decisions to preserve the financial and economic stability and viability of business entities in modern conditions. Among the currently existing developments, the most difficult place is the formation of the methodology for the formation of the system of evaluation indicators, as well as the justification of their limit (critical) values. The scientific novelty of the research results lies in the identification of the composition of indicators in three areas: resource availability, efficiency and sustainability, the ability of the business entity to develop. In terms of determining the limit values of indicators, it is advisable to combine approaches: payback of costs, payback of own capital, break-even, standard values of financial ratios and comparison with average industry values.